2019
DOI: 10.1186/s13244-019-0787-6
|View full text |Cite
|
Sign up to set email alerts
|

Can imaging be the new yardstick for diagnosing peripheral neuropathy?—a comparison between high resolution ultrasound and MR neurography with an approach to diagnosis

Abstract: PurposePeripheral neuropathies are a group of disorders which affect the peripheral nervous system which have been conventionally diagnosed using electrodiagnostic studies. This study was carried out to assess the role of imaging in diagnosing peripheral mononeuropathy as exact anatomical localisation of the pathology is possible using high-resolution ultrasound and MR neurography, the modalities assessed in this study.MethodA hospital-based prospective analytical study was carried out in a resource-limited se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 33 publications
(35 reference statements)
1
18
1
2
Order By: Relevance
“…Our study has shown MRN to be more accurate in detecting the peripheral nerve pathologies (89.3 vs. 82.9%) with higher negative predictive values for diagnosing the lesions. Similar findings were noted in a comparative study published by Agarwal et al, 8 who also reported higher accuracy of MRI over HRUS (93.89 vs. 86.11%) with higher negative predictive value of MRI. The confidence levels to detect pathological characters like caliber change ( p = 0.007) and nerve discontinuity ( p = 0.009) were higher with HRUS than MRI (100 vs. 50% and 100 vs. 70%, respectively) and found to be statistically significant ( p <0.05).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study has shown MRN to be more accurate in detecting the peripheral nerve pathologies (89.3 vs. 82.9%) with higher negative predictive values for diagnosing the lesions. Similar findings were noted in a comparative study published by Agarwal et al, 8 who also reported higher accuracy of MRI over HRUS (93.89 vs. 86.11%) with higher negative predictive value of MRI. The confidence levels to detect pathological characters like caliber change ( p = 0.007) and nerve discontinuity ( p = 0.009) were higher with HRUS than MRI (100 vs. 50% and 100 vs. 70%, respectively) and found to be statistically significant ( p <0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Agarwal et al 8 also reported higher specificity with MRI (86.67 vs. 80%) with higher positive predictive values; however, in our study HRUS showed higher positive predictive value (100 vs. 95%) with higher specificity (100 vs. 66.6%), which can be attributed to poor image quality for MRN in few of our patients with metallic implants or movement artifacts and use of high-resolution sonographic probe. Zaidman et al 11 found specificity to be similar with both modalities, while Garg et al 9 have not evaluated both for the same.…”
Section: Discussioncontrasting
confidence: 81%
“…[14][15][16] In recent years, several MR sequences have been tried for peripheral nerve diseases. [17][18][19] However, they fail to provide objective parameters to re ect intrinsic characteristics of nerve. Readout-segmented DTI was thus introduced by us as a new way to assess peripheral nerve, as it could provide quantitative parameters including FA and ADC.…”
Section: Discussionmentioning
confidence: 99%
“…16 Deviations from the norm may be interpreted as signs of an underlying condition. [17][18][19] For example, findings of chronic nerve entrapment on MRN include nerve swelling proximally and sometimes distally with an abrupt transition to a flattened contour at the entrapment site. 20 Aggarwal et al described a case of an 18-year-old man presenting with a medial epicondyle fracture and elbow dislocation treated via closed reduction of the elbow and cast immobilization.…”
Section: Upper Extremity Nerve Entrapmentsmentioning
confidence: 99%